2022
DOI: 10.1161/hypertensionaha.121.17765
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Four–Hour Central (Aortic) Systolic Blood Pressure: Reference Values and Dipping Patterns in Untreated Individuals

Thomas Weber,
Athanase D. Protogerou,
Mohsen Agharazii
et al.

Abstract: Central (aortic) systolic blood pressure (cSBP) is the pressure seen by the heart, the brain, and the kidneys. If properly measured, cSBP is closer associated with hypertension-mediated organ damage and prognosis, as compared with brachial SBP (bSBP). We investigated 24-hour profiles of bSBP and cSBP, measured simultaneously using Mobilograph devices, in 2423 untreated adults (1275 women; age, 18–94 years), free from overt cardiovascular disease, aiming to develop reference values and to analyze daytime-nightt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 67 publications
0
20
0
1
Order By: Relevance
“… 29 With advanced technology, simultaneous ambulatory monitoring of brachial and central hemodynamics is now available for clinical use. 23 Given large amount of evidence showed that the 24‐h ambulatory BP was a better cardiovascular risk predictor than the office BP, irrespective of at brachial 35 or central 36 , 37 , 38 sites, it is warranted to explore if the ambulatory central BP outperforms ambulatory brachial BP in risk stratification and hypertension management. Ultimately, direct interventional evidence is needed to demonstrate whether targeting central hypertension with an optimized antihypertensive drug treatment would be beneficial beyond the control of brachial hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 29 With advanced technology, simultaneous ambulatory monitoring of brachial and central hemodynamics is now available for clinical use. 23 Given large amount of evidence showed that the 24‐h ambulatory BP was a better cardiovascular risk predictor than the office BP, irrespective of at brachial 35 or central 36 , 37 , 38 sites, it is warranted to explore if the ambulatory central BP outperforms ambulatory brachial BP in risk stratification and hypertension management. Ultimately, direct interventional evidence is needed to demonstrate whether targeting central hypertension with an optimized antihypertensive drug treatment would be beneficial beyond the control of brachial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…29 With advanced technology, simultaneous ambulatory monitoring of brachial and central hemodynamics is now available for clinical use. 23 Given large amount of evidence showed that the 24-h ambulatory BP was a better cardiovascular risk predictor than the office BP, irrespective of at brachial 35 or central [36][37][38]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed specific analyses to detect potential sex effect on our results; however, none of these revealed a role of sex in the association of BP indices with arterial damage. Given the well-described central hemodynamic differences between men and women 35 and the very recently described differences in 24-hour aortic hemodynamics, 36 we suggest that further studies in larger populations should also examine a potential sex effect on the association of 24-hour aortic hemodynamics with vascular function, which cannot be negated by the present finding due to sample size limitations. Moreover, since this is a cross-sectional study, no conclusions can be drawn on the clinical implications and prognostic value of this methodology and no extraction of causal relationships can be made.…”
Section: Discussionmentioning
confidence: 53%
“…In the 24-h ambulatory blood pressure (ABP) study, 24-h central ABP, measured with regular brachial cuffs and dedicated software, tends to be superior to 24-h brachial ASBP in predicting organ damage related to the heart, which is LV hypertrophy ( 35 ). Additionally, these researchers suggest upper normal limits for 24-h central SBP of 135 mmHg and for 24-h central SBP of 120 mmHg as measured by invasive and non-invasive gold standard methods ( 36 ).…”
Section: Discussionmentioning
confidence: 99%